2009
DOI: 10.1117/1.3079803
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon sensor with enhanced sensitivity using top nano dielectric layer

Abstract: Increasing the sensitivity of surface plasmon resonance (SPR) sensors is important to enable controlling small concentrations of materials in liquid solutions or for gas sensing. Upon using a 10-15 nm top layer of dielectric film with a high value of the real part ′ ε of the dielectric function, on top of an SPR sensor in the Kretschmann configuration, the sensitivity is improved by few times. The imaginary part ′′ ε of the top nano layer permittivity needs to be small enough in order to reduce the losses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…This technique can reduce the number of steps and time needed to perform the assays. Other researchers have concentrated on different refinements of detection such as spatially resolved measurements [116], miniaturization [117,118], increased sensitivity [118,119], and microarrays to perform high-throughput multiple assays [120].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique can reduce the number of steps and time needed to perform the assays. Other researchers have concentrated on different refinements of detection such as spatially resolved measurements [116], miniaturization [117,118], increased sensitivity [118,119], and microarrays to perform high-throughput multiple assays [120].…”
Section: Applicationsmentioning
confidence: 99%
“…The addition of a dielectric layer [64,119] between the metal and the analyte to be sensed has several benefits: the metal layer is protected, the field intensity is increased at the interface, and, as a result, sensitivity is increased. A thick layer [64] of an additional dielectric layer also allows for excitation with both s-and p-polarized light.…”
Section: Applicationsmentioning
confidence: 99%
“…Refractive index (n) Extinction coefficient (k) References SF-11L glass 1.73205 0 [14] Ag 0.13 3.99 [14] Si 3.92 0.01 [14] AlAs 3.112 0 [15] TiO 2 2.2789 0 [18] Si 3 N 4 2.019 0 [15] Water 1.33 0 [14] Figure 3. Sensitivity as a function of dielectric film thickness for the NGWSPR sensor with Si, AlAs, TiO 2 , or Si 3 N 4 film.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been demonstrated that under the condition of the same thickness of the dielectric film a NGWSPR sensor with a higher refractive index dielectric film can achieve higher sensitivity, [15,19] it is still doubtful whether the dielectric film with higher refractive index is more beneficial for the sensitivity improvement, because the sensitivity of a NGWSPR sensor can be further improved by optimizing the thickness of the dielectric film. [20] So, to achieve the maximum sensitivity for a NGWSPR sensor, the material (or refractive index) and the thickness of the top dielectric film need to be optimized simultaneously, which has not been studied until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation